2008
DOI: 10.1590/s0006-87052008000100004
|View full text |Cite
|
Sign up to set email alerts
|

Variação espaço-temporal do índice de área foliar e brix em cana-de-açúcar

Abstract: RESUMOOs objetivos do trabalho foram estudar a variação espaço-temporal do índice de área foliar (IAF) e do teor de sólidos solúveis (Brix) na cana-de-açúcar, em Piracicaba (SP) ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…The intercepted light fraction is determined by the Leaf Area Index (LAI = leaf area/ soil area) (Watson 1947), which varies significantly in each sugarcane development stage (Almeida et al 2008), especially due to accumulated degreedays (Teruel et al 1997). Moreover, there is spatial and environmental variation in growth (Scarpari & Beauclair 2008). Taking into account the importance of leaf area in monitoring agricultural crops, such as sugarcane 1.…”
Section: Introductionmentioning
confidence: 99%
“…The intercepted light fraction is determined by the Leaf Area Index (LAI = leaf area/ soil area) (Watson 1947), which varies significantly in each sugarcane development stage (Almeida et al 2008), especially due to accumulated degreedays (Teruel et al 1997). Moreover, there is spatial and environmental variation in growth (Scarpari & Beauclair 2008). Taking into account the importance of leaf area in monitoring agricultural crops, such as sugarcane 1.…”
Section: Introductionmentioning
confidence: 99%
“…There is a tendency of reduction in the degree Brix when the amount of irrigation is increased and the reduction of the ETpc (%) is reduced. This is due to the higher dilution of soluble solids (sugars) in the broth due to the larger amount of water available in the soil and, consequently, in the stems, due to the higher irrigation depth applied, confirming Scarpari and Beauclair (2008). These authors observed that in areas where water availability is higher, ºBrix values are lower because of the dilution of sugars.…”
Section: Resultsmentioning
confidence: 55%
“…Teor de sólidos solúveis (ºBrix) (A) e de fibra (B) da cana-de-açúcar (cana-planta), variedade RB92579, em função das lâminas de irrigação aplicadas A redução do teor de sólidos solúveis verificadas com o aumento das lâminas de irrigação deve-se provavelmente a diluição mais acentuada dos sólidos do caldo em detrimento da maior disponibilidade de água no solo e, consequentemente, maior concentração no colmo, proporcionada pelo aumento das lâminas de irrigação aplicadas. A esse respeito, Scarpari e Beauclair (2008) verificaram que os menores valores de °Brix são encontrados em localidades de maior abundância de água, fato este justificado pela dissolução dos açúcares, indicando atraso da maturação. Oliveira et al (2011) também verificaram decréscimos no teor de sólidos solúveis da cana-deaçúcar quando submetida a diferentes regimes hídricos.…”
Section: Figuraunclassified